1998
DOI: 10.1123/jsr.7.4.300
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intratester Reliability of Lower Extremity Circumference Measurements

Abstract: The purpose of this study was to examine the inter- and intratester reliability of lower extremity circumference measurements obtained by two testers using the same tape measure and two different tape measures. Twenty-one male high school student-athletes participated in this study. Two testers measured lower extremity circumference at three sites using a standard flexible tape measure and a Lufkin tape measure with a Gulick spring-loaded handle attachment. Measurement sites were medial joint line, 20 cm above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The reliability of cirumference measurments varies according to the type of tape measure being used. ICC ranges from 0.92 to 0.99 have been found with a Lufkin/Gulick spring loaded being more reliable than a standard synthetic tape measure (Harrelson et al 1998). The authors recommend not using the standard tape when more than one person is making measurements due to increased intertester error.…”
Section: Volume (Ml)mentioning
confidence: 94%
“…The reliability of cirumference measurments varies according to the type of tape measure being used. ICC ranges from 0.92 to 0.99 have been found with a Lufkin/Gulick spring loaded being more reliable than a standard synthetic tape measure (Harrelson et al 1998). The authors recommend not using the standard tape when more than one person is making measurements due to increased intertester error.…”
Section: Volume (Ml)mentioning
confidence: 94%
“…Measurements of the circumference of both thighs at 5 cm above the upper edge of the patella were taken for a follow‐up using a reliable and clinically approved spring tape device (23,24). This procedure was repeated every three days (from the day of admission) in both, ES and control.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, we have reported the repeatability (ICC and CV) of measurements, which were generally very high. The high within-and between-day reliability of tape measure (Harrelson et al, 1998), water displacement volumetry (Brijker et al, 2000;Moholkar & Fenelon, 2001;Pasley & O'Connor, 2008), segmental bioelectrical impedance analysis (Yamada et al, 2010(Yamada et al, , 2017, and ultrasound shearwave elastography (Lacourpaille et al, 2012;Sasaki et al, 2014) has also been reported elsewhere. Thus, it is highly unlikely that the lack of control condition seriously affects the significance of our findings.…”
Section: Limitationsmentioning
confidence: 67%